Ambient assisted living : 9. AAL-Kongress, Frankfurt/M, Germany, April 20-21, 2016 - Wichert, Reiner; Mand, Beate (Advanced technologies and societal change., 2017)
In this book, leading authors in the field discuss the habitats of tomorrow. These habitats will be connected through autonomous and assistive systems, turning habitats into health resorts. This book discusses how assistance technologies enable a smooth transition from comfortable health support to medical or nursing care. The contributions have been chosen and invited at the 9th AAL congress, Frankfurt.